Students’ perception on preventive archaeological research in Timisoara - Atalia Onițiu; Mariana Balaci (Academicus International Scientific Journal, 2024)

(untitled)
The research that has been carried out in recent years in the historical area of Timisoara constituted the context for conducting a sociological study regarding the perception of permanent residents and visitors of Timisoara, on these studies, both in terms of the legislative framework in which preventive archaeological investigations are carried out, their way of organization, but especially regarding their impact on the cultural heritage of the city. A separate category of subjects, individualized within the target group of the research, are the students. Our analysis follows the perception of 360 students, highlighting both their level of information and knowledge regarding the archaeological research carried out in Timisoara, but also their opinions regarding the impact and usefulness of this type of investigation for the cultural heritage and for the city of Timisoara. After analyzing the results, we could find that most students expressed themselves in favor of this type of archaeological investigation, perceived as necessary and useful, with an impact especially on local history, which should be restored and valued. The conclusions of the study are important in our opinion, as they reflect the perception of a significant category of the population, namely students (mostly young people, aged between 18-28).